Gelling properties of myofibrillar protein–soy protein and k-carrageenan composite as affected by various salt levels. Issue 1 (1st January 2019) - Sun, Jie; Yin, Guoyou; Chen, Jie; Li, Pengpeng
ABSTRACT: In order to increase use of soybean protein in meat products, the objective of this research was to investigate the effects of k-carrageenan on the gel properties of the myofibrillar protein (MP)–soybean protein isolate (SPI) composite with various salt levels. The results showed that the addition of SPI in a small amount improved the gelation and WHC of MP-SPI composite gel, and incorporation of k-carrageenan enhanced WHC at low NaCl concentration (0.1 mol/L and 0.3 mol/L). The observation results of the environmental scanning electron microscope (ESEM) suggested that the strong WHC of k-carrageenan and the filling of soybean protein promoted the gelation forming. It was related to the positive effects on the elastic modulus, gel strength and WHC of MP mixing with a small amount of soybean protein and larger content of k-carrageenan. However, at a high salt concentration (0.6 mol/L), SPI showed negative effects on the gel strength and WHC of composite MP-SPI. The gel strength and WHC of mixed MP-SPI were reinforced with the addition of k-carrageenan. In conclusion, the results of this research showed that the interactions in the system of the k-carrageenan-MP-SPI composite were significantly influenced by salt concentration. Low concentration of soybean protein and high level of k-carrageenan at low-salt concentration improved composite gel properties.